The Shifting of Representation: from a Female Regent Presence to The Policy Interest of Rural Women - Siti Mauliana Hairini; Noviana Sari (Scholar Center, 2023)
Exclusively, The theoretical and empirical studies on women's representation have focused on parliament and the existing literature on women in politics. The substantive representation become one of the main concerns of the scholars to be an instrument of how to pursue women's issues while, this paper has tried to analyze how the descriptive representation and the substantive representation are inseparable from female regent existence in politics. In the debate between descriptive representation and substantive representation of women in pursuing conservative political issues for rural women, this study considers that there is a causal relationship between the two representation models. The politics of presence and ideas of female Regent who implemented electronic voting (e-voting) in simultaneous village head elections in Barito Kuala District has strongly created a symbol for women that indirectly fostered a sense of commons destiny and experience for women to encourage their participation and increase the electability of women in village politics.